Vegetation Cover of Ain Mara in Jabal Al Akhdar, Libya - المقصي فرج محمد; مخلوف محمد الهادي (The Libyan Journal of Science, 2020)
This study aimed to assess the current status of vegetation cover and biological diversity in the ‘Aīn Māra region of Jabal Al Akhdar. The study was conducted in the period between 2018-2019 for two consecutive growth seasons. In this survey a total of 161 plant species were collected and identified belonging to 148 genera and 73 families. The results showed the dominance of the family Fabaceae, represented by 13 species, followed by the Asteraceae with 10 species. Of the total number, 118 species were found to be growing wild and 43 cultivated. The lifeform analysis showed the dominance of trees and shrubs with a percentage of 43%, followed by annual herbaceous plants with a percentage of 32%. In addition, 6 endemic species were collected and identified which are, Cyclamen rohlfsianum Arbutus pavarii Arum cyrenaicum ،Onosma cyrenaicum ،Cupressus sempervirens var. Horizontalis ،Origanum cyrenaicum